Marketing Model of Islamic Education Services in Facing PPDB - Wulandari, Wiwin; Harsono, Harsono; Suyatmini, Suyatmini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The New Student Admission Program (PPDB) is currently carried out by the government through a zoning system with the aim of achieving equitable distribution of education quickly and with quality. The zoning system takes into account the distance between the student's house and the school. The existence of a zoning system also has an impact on the emergence of competition in educational institutions. During the Covid-19 pandemic, many parents chose to send their children to the nearest public school and this had an impact on private schools. SMP Al Qolam Muhammadiyah Gemolong was not affected by the policy and even got an increase in registrants. The role of the marketing team that carries out marketing management strategies correctly results in new student applicants exceeding the target. The research problem is how the marketing model of Islamic education deals with PPDB. This is qualitative research with an ethnographic design. Collecting data using the method of observation, interviews and documentation. The analysis technique is data organized in the site. The results show that users of educational services are involved in policy making and planning in schools, so users of educational services also determine the development of institutions that affect student development. In the planning process there is a process of determining the direction of the goal. The marketing team of SMP Al Qolam Muhammadiyah Gemolong uses the concept of organized management. There are two forms of planning, namely internal and external marketing. The marketing concept includes the 7Ps, namely product, price, place, promotion, people, physical evidence, and process. Whereas in achieving its success, the marketing team of SMP Al Qolam Muhammadiyah Gemolong uses several marketing models including Production Insight Marketing Concepts, Product Insight Marketing Concepts, Selling Insight Marketing Concepts, Marketing Insight Concepts, Community Insight Marketing Concepts.